Maternal urban particulate matter exposure and signaling pathways in fetal brains and neurobehavioral development in offspring. (30th May 2022) - Li, Shuman; Liu, Yongjie; Liu, Bin; Hu, Yun-Qing; Ding, Yu-Qiang; Zhang, Jun; Feng, Liping
Abstract: It is well understood that exposure to particulate matter (PM) can have adverse effects on the nervous system. When pregnant women are exposed to PM, their fetuses are also affected through the placenta. However, the mechanisms by which fetal brain development is regulated between mother and fetus remain unclear. C57BL/6J pregnant mice were exposed to PM at embryonic day (E) 2.5, 5.5, 8.5, 11.5, 14.5, and 17.5 via nasal drip at three doses (3, 6, 12 mg/kg of body weight) or PBS control. Neurobehavioral changes in the offspring were examined at 5–6-week-old by open field test (OFT) and elevated plus maze (EPM). The maternal and fetal brain and placenta were collected at E18.5, and molecular signal changes were explored using transcriptome analysis. We found that both male and female low-dose pups and male middle-dose pups traveled a significantly longer distance than controls in EPM tests. Both male and female low-dose pups showed a higher frequency of entering the center area and female low-dose pups exhibited a higher percentage of distance moved in the center area than controls in OFT tests. Gene expression in the maternal brain, fetal brain, and placenta at E18.5 was altered. Differentially expressed genes were enriched in the neuroactive ligand-receptor interaction pathway in all three tissue types. Pathway analysis revealed that the PI3K-Akt and PKC signaling was dysregulated in the fetal brain in the high-dose group compared with the control group. The pathways play a role in neuronal survival and apoptosis. Furthermore, there is a dose-dependent increase in Caspase-6, neuronal apoptosis and neurodegeneration biomarker, levels in E18.5 fetal brain ( P  = 0.06). In conclusion, our study demonstrated that prenatal PM exposure enhanced exploration and locomotor activity in adolescent offspring and altered molecular events in maternal brain, fetal brain, and placenta. The connections of these changes warrant further investigations. Graphical Abstract: ga1 Highlights: ● Particulate matter exposure was conducted in pregnant mice. ● Gene expression was altered in the maternal brain, fetal brain, and placenta. ● Neuroactive ligand-receptor interaction pathway was disrupted in all 3 tissue types. ● PI3K-Akt and PKC signaling were disrupted in the fetal brain. ● Adolescent offspring showed an enhanced exploration and locomotor activity.